1988
DOI: 10.1021/jo00240a018
|View full text |Cite
|
Sign up to set email alerts
|

p,p'-Dinitrobenzhydryl ethers, acid and base stable protecting groups, which are readily removable in the presence of benzyl and monomethoxytrityl functions

Abstract: 4-(Benzyloxy)-2-fluoro-2-methylbutan-l-ol (3f): 0.69 g (31%); Rf 0.15 (hexanes/ethyl acetate, 3:1);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Carbenes, on the other hand, are reported to insert with high efficiency into O–H and C–H bonds but we found in preliminary investigations that diaryldiazomethanes do not necessarily exhibit high reactivity in solution despite their reported reactivity with carboxylic acids, alcohols, amines, and alkenes, amongst other functional groups . We wondered if the incorporation of electronically modifying groups might give an acceptable balance of stability and reactivity, favouring insertion into low surface energy polymers, and preliminary work with methoxy‐activated systems 1 (R = OMe) indicated that although polymer modification was possible, even more reactive systems would be desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Carbenes, on the other hand, are reported to insert with high efficiency into O–H and C–H bonds but we found in preliminary investigations that diaryldiazomethanes do not necessarily exhibit high reactivity in solution despite their reported reactivity with carboxylic acids, alcohols, amines, and alkenes, amongst other functional groups . We wondered if the incorporation of electronically modifying groups might give an acceptable balance of stability and reactivity, favouring insertion into low surface energy polymers, and preliminary work with methoxy‐activated systems 1 (R = OMe) indicated that although polymer modification was possible, even more reactive systems would be desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we decided to examine the behavior of alternative starting materials replacing secondary amides by tertiary amides or esters. Due to poorly efficient O‐propargylation of ethyl mandelate under our conditions, we decided to prepare O‐propargyl ester 6 using a BF 3 triggered reaction of diazoester 5 as reported by Just et al (Scheme ) . When 6 was treated under our optimized cyclization conditions, the expected 2,5‐dihydrofuran 7 was not formed but we could isolate out of the complex mixture the 2,5‐dihydrofuran 8 obtained in a low 12 % yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…It will be an exciting challenge for the future to synthesize longer RNA fragments of high quality using these new protected protecting groups, approach and the corresponding easy workup procedures. 2 (14). According to 2.1, from 2 with 6.…”
Section: Isolation Of Partially and Fully Deprotectedmentioning
confidence: 99%
“…There are practical solutions of the problem leading to longer RNA sequences [2 ± 6] since, for 2'-OH protection, the tbds ((tert-butyl)dimethylsilyl group) [7 ± 9] or the fpmp (1-(2-fluorophenyl)-4-methoxypiperidin-4-yl) [6] [10] residue can be used. Still, some side reactions [10] [11] have to be overcome, especially when other blocking groups such as the 2-nitrobenzyl (nbn) [12], the dianisoyltrichloroethyl (date) [13], the 4,4'-dinitrobenzhydryl (dnbh) [14], the [2-(4-nitrophenyl)ethyl]sulfonyl (npes) [15], or the acetal functions tetrahydro-2H-pyran-2-yl (thp) [16], tetrahydro-4-methoxy-2H-pyran-2-yl (mthp) [17], [(trimethylsilyl)ethoxy]ethyl (see) [18], 3-methoxy-1,5-bis(methoxycarbonyl)pentan-3-yl (mdmp) [19 ± 21], 1-alkoxyethyl-and 1-(2-chloroethoxy)ethyl (cee) [22] are applied.…”
mentioning
confidence: 99%